Design Thinking, Pemikiran Kreatif Dalam Pembuatan Dan Pengembangan Konten Streaming Online Di RGI Al Azhar - Gora, Radita; Muqsith, Abdul; Misbah, Nuril Ashiva`; Hapsari, Dian Tri (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Graphic design or video editing that can be operationalized using mobile devices (smart phones) using applications found in the store on smartphone devices such as the Play Store (Android) or Ios (Apple) that uses a computing system and is equipped with cloud computing access that functions as well as machine learning, it makes it very easy for everyone to create works and produce content through their respective mobile devices without having to use high-spec computer devices. Therefore, graphic design training with Canva and video editing with Kinemaster aims to foster students/I RGI Al Azhar, Depok to be able to produce graphic works both visual graphics in the form of still images and also manage multimedia content with mobile devices such as editing images, adding and image design, and video editing can be done easily, practically and anywhere as part of the student's debriefing when working later.